Effects of lazaroid U-74389G on intestinal ischemia and reperfusion injury in porcine experimental model. (January 2015) - Flessas, Ioannis; Bramis, Ioannis; Menenakos, Evangelos; Toutouzas, Konstantinos; Agrogiannis, George; Patsouris, Efstratios; Nonni, Afroditi; Chrysikos, Dimosthenis; Korontzi, Maria; Gioxari, Aristea; Zografos, George; Papalois, Apostolos
Abstract: Background : The readmission of molecular oxygen into an ischemic tissue promotes the oxidation of resuscitated tissue with certain pathophysiologic mechanisms.Materials and methods : Twenty four pigs (male or female) were randomized in this study. The animals were allocated to four groups with an equal number ( n = 6) in each group: 1) control group-ischemia for 30 min and reperfusion for 60 min. 2) control group-ischemia for 30 min and reperfusion for 120 min. 3) ischemia for 30 min and immediate iv injection of lazaroid U-74389G and reperfusion for 60 min. 4) ischemia for 30 min and immediate iv injection of lazaroid U-74389G and reperfusion for 120 min.Results : We investigated further the role of an antioxidant molecule such as U-74389G and we concluded that there is statistically significant relation in MDA (malondialdeyde), TNF –α (tumor necrosis factor-α) measurement in tissue, while the histological score in the groups that the lazaroid was administered was improved.Conclusions : In many emergency clinical situations, such as reperfusion of the intestine, the role of U-74389G can be protective. Highlights: The MDA in the groups that the lazaroid was used was decreased in comparison with the final time groups without U-74389G. The TNF was decreased in the two groups 60 rep + drug, 120 rep + drug compared to groups without U-74389G administration. In the group 120 rep + drug, where the lazaroid was administrated the histopathology score was significantly reduced.